Measuring The Cost Of The Financing Structure For The Banking Sector In Iraq. An Empirical Study For A Sample Of Banks Which Are Listed In Iraqi Market For Financial Securities - Hadi Abdulameer, Hussein; Abbas Al- Janabi, Hayder; Ali Khaleel, Ameer (Opción, 2019)
A financing structure is a combination of the proprietary finance and the borrowed finance. There is a wide range of available options in front of the companies to increase their capital. A set of special models have been de- veloped to estimate the optimal debt ratio of the institution. The research ex- amines how institutions can use the available information to them to choose the suitable mixture of proprietary finance and the borrowed finance that the companies use to finance investments, and illustrate what are the financing tools that can be used to reach to the intended mixture. To be more specific, it has been tested whether the institutions should determine the percentage of ownership that it sees as optimal one and then to move to the debt ratio until the financing structure is completed and the funds would be available for in- vestment and performing the tasks. The process of forming the necessary fi- nancing has been accompanied with a set of risks, the most important of which is the excessive reliance of the institution on the borrowed finance and thus leads to the stumbling in paying its obligations towards others. Consequently, it may be exposed to the financial difficulty, then to bankruptcy and exit from competition. The institution which decides to move from the current debt level to a combination of optimal financing has two decisions must it makes. First, it has to think in the speed at which it wants to move. In this case, the degree of determination will vary greatly between institutions, depending on the amount of threat that it expected from the fact that the borrowed finance is less (or exaggerated). The second decision is that whether it is necessary to increase (or decrease) the debt ratio by recapitalizing investments, stripping assets and using cash money to reduce the debt or property rights, and in- vesting in new projects financed by debt or stocks, or changing the politics of profits distribution.